2022
DOI: 10.1038/s41467-022-33277-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into molecular mechanism for N6-adenosine methylation by MT-A70 family methyltransferase METTL4

Abstract: METTL4 belongs to a subclade of MT-A70 family members of methyltransferase (MTase) proteins shown to mediate N6-adenosine methylation for both RNA and DNA in diverse eukaryotes. Here, we report that Arabidopsis METTL4 functions as U2 snRNA MTase for N6−2’-O-dimethyladenosine (m6Am) in vivo that regulates flowering time, and specifically catalyzes N6-methylation of 2’-O-methyladenosine (Am) within a single-stranded RNA in vitro. The apo structures of full-length Arabidopsis METTL4 bound to S-adenosyl-L-methioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…m6A modification is reversibly modulated through the installation of methyl transferases (writers), the removal of a methyl group by demethylases (erasers), and the recognition of m6A binding proteins (readers) [ 22 , 23 ]. m6A writers and associated proteins (m6A writer complex) include Vir-like m6A methyl transferase-associated protein (VIRMA) [ 24 ], methyl transferase-like protein 3 (METTL3) [ 25 ], METTL4 [ 26 ], MTTL5 [ 27 ], METTL14 [ 28 ], METTL 16 [ 29 ], Wilms’ tumor 1 associated protein (WTAP) [ 30 , 31 ], RNA-binding motif protein 15/15B (RBM15/15B) [ 32 ], casitas B-lineage lymphoma-transforming sequence-like protein 1 (CBLL1) [ 33 ], zinc finger CCCH-type containing 13 (ZC3H13), and zinc finger CCHC-type containing 4 (ZCCHC4) [ 5 , 34 , 35 , 36 , 37 , 38 ]. RBM15/15B, VIRMA, CBLL1, ZCCHC4, and ZC3H13 act as associated proteins of m6A writers.…”
Section: Regulators Of Rna Methylationmentioning
confidence: 99%
“…m6A modification is reversibly modulated through the installation of methyl transferases (writers), the removal of a methyl group by demethylases (erasers), and the recognition of m6A binding proteins (readers) [ 22 , 23 ]. m6A writers and associated proteins (m6A writer complex) include Vir-like m6A methyl transferase-associated protein (VIRMA) [ 24 ], methyl transferase-like protein 3 (METTL3) [ 25 ], METTL4 [ 26 ], MTTL5 [ 27 ], METTL14 [ 28 ], METTL 16 [ 29 ], Wilms’ tumor 1 associated protein (WTAP) [ 30 , 31 ], RNA-binding motif protein 15/15B (RBM15/15B) [ 32 ], casitas B-lineage lymphoma-transforming sequence-like protein 1 (CBLL1) [ 33 ], zinc finger CCCH-type containing 13 (ZC3H13), and zinc finger CCHC-type containing 4 (ZCCHC4) [ 5 , 34 , 35 , 36 , 37 , 38 ]. RBM15/15B, VIRMA, CBLL1, ZCCHC4, and ZC3H13 act as associated proteins of m6A writers.…”
Section: Regulators Of Rna Methylationmentioning
confidence: 99%
“…METTL3, a 70 kDa protein also named MT-A70, was first identified and isolated from mammalian cell nuclear extracts in 1997 [ 6 ]. It belongs to the conserved family of methyltransferases, possessing a methyltransferase domain [MTD] that catalyzes methyl transfer to adenosine [ 6 ]. The N-terminus of METTL3 contains two Cys-Cys-Cys-His (CCCH)-type zinc finger (ZnF) motifs common in RNA-binding proteins [ 7 ].…”
Section: Structure and Function Of Mettl3mentioning
confidence: 99%
“…Instead, FIO1 installs m 6 A into U6 small nuclear (sn)RNA, a small subset of poly(A) + RNA, and several phenotype-related mRNAs, thereby regulating the mRNA stability and many developmental processes [ 62 ]. Another example of independent methyl transferase that is found in Arabidopsis is MTC (an orthologue of METTL4) [ 63 ]. The structural comparison revealed that Arabidopsis MTC homodimer shared similar features with the METTL3-METTL14 heterodimer, suggesting that MTC functions as the m 6 A writer [ 63 ].…”
Section: M 6 a In Plantsmentioning
confidence: 99%
“…Another example of independent methyl transferase that is found in Arabidopsis is MTC (an orthologue of METTL4) [ 63 ]. The structural comparison revealed that Arabidopsis MTC homodimer shared similar features with the METTL3-METTL14 heterodimer, suggesting that MTC functions as the m 6 A writer [ 63 ]. MTC displayed N6 −2′-O-dimethyladenosine (m 6 Am) in vivo and N6 -methylation of 2′-O-methyladenosine (Am) within single-stranded RNA in vitro [ 63 ].…”
Section: M 6 a In Plantsmentioning
confidence: 99%
See 1 more Smart Citation